Commercial use of trusts in the English legal system - Michalíková, Jana; Boháček, Martin, 1947-; Husták, Zdeněk, 1973-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2009)
Thesis describes the use of English trusts in commercial environment. First part defines the concept of trust, elements of trust and various types of trusts. Second part defines different commercial situations where trusts may be used and advantages of the use of trusts for commercial people. Third part considers chosen institutes in the Czech laws, which have some common features with trusts.
Vedoucí práce: Martin Boháček
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2010
Rok obhajoby 2010
Keywords: podnikání a právo [obor dipl. práce]; diplomové práce; master's theses